Pengaruh Dewan Komisaris Independen, Komite Audit, Public Ownership, Dan Risk Minimization Terhadap Pengungkapan Corporate Social Responsibility: Studi Kasus pada Perusahaan Industri Primer yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Margareth, Anggita; Murti, Galuh Tresna (eProceedings of Management, 2024)
Corporate social responsibility (CSR) refers to a company's efforts to fulfill social and environmentalresponsibilities. Companies should consider the local community and environment affected by their businessactivities. Disclosure of CSR information allows the public to evaluate a company's performance based on itspositive contribution to society and the environment. This study aims to test the influence of the independent boardof commissioners, audit committee, public ownership and risk minimization on CSR disclosure This study appliesquantitative methods and data panel regression as analysis techniques, and uses E-views 12 software to processthe data. Companies listed on the Indonesia Stock Exchange from 2019 to 2022 are the subjects of this study. Thepurposive sampling technique was used in this study which produced 19 samples over a period of 4 years with atotal of 76 observational data. The findings of this study found that the independent board of commissioners, theaudit committee, public ownership and risk minimization simultaneously affect CSR disclosure. Overall, theindependent board of commissioners, the audit committee and public ownership do not affect CSR disclosure. Onthe other hand, CSR disclosure is greatly influenced by risk minimization. This study is aimed at helping investorsmake better investment decisions. The researcher suggested that the researcher then look at other independentvariables that affect CSR disclosure by changing the research object and adding the latest research year. Keywords-corporate social responsibility disclosure, independent board of commissioners, audit committee,public ownership, risk minimization.